Study the Effect of Cold and Hot Water Extracts of Parsley Plant Petroselinumcrispum on the Growth of some Enterobacteriaceae - Mohammad, May H (Al-Nahrain Journal of Science, 2018)
This study was conducted to determine the effect of hot and cold water extractsof parsley leaves on five genus of bacteria belong toenterobacteriaceae familynomely; E.coli, Enterobacter, Klebsiella, Shigellaand Salmonella after 24 or 48 hrs of incubation where the number of growth colonies on macConkey agar appears. The efficiency of these extractsto prevent bacteria from growthwas indicated by using the percentage ofdilution value. The resultsshowed that the hot water extract was more efficientin most treated bacteria compared with cold water extract. Also resultsindicated that both Salmonella andEnterobacterwere more sensitive toward both extracts incomparsion with other studied bacteria, such asKlebsiellashowed higher resistance toward both extracts. Additionally, significant differencesbetween number of colonies grown on MacConkeymedium that treated with hot or cold water extracts were recorded.